Critical size defect in a rat calvaria model using trephination: An animal model for investigating potential bone regenerative scaffolds - Jeffrey Huang; Jithendra Ratnayake; George J. Dias (MethodsX)
Animal studies have been a key in vivo investigation in translating bioregenerative material into human clinical trials. The critical size defect (CSD) in a rat’s calvaria is a popular methodology for demonstrating and investigating the regenerative properties of a biomaterial. Various surgical approaches have been discussed in the literature on creating CSD and can vary based on species, age and anatomical location. This paper aims to provide a reliable and reproducible step-by-step guide for creating a critical-size defect on the calvaria of a laboratory rat using trephination. This paper will: • Cover the surgical approaches and management in the pre-, intra- and post-operative phases. • Provide figures to help visually guide readers in carrying out the operation. • Cover basic general anaesthetic issues and resolutions.